PEMBUATAN KOMPOSIT ZnO-ARANG AKTIF SEBAGAI FOTOKATALIS UNTUK MENDEGRADASI ZAT WARNA METILEN BIRU - Wismayanti, Dewa Ayu; Diantariani, Ni Putu; Santi, Sri Rahayu (Jurnal Kimia (Journal of Chemistry); Vol. 9, no. 1 Januari 2015, 2015)
Preparation of ZnO-activated carbon composite with a mass ratio of ZnO : activated charcoal of 5:2; 5:1 and 15:2 have been carried out using the sol-gel method The characterisation of  ZnO-activated carbon composite was done by using  X-Ray Diffraction (X-RD) and Fourier Transform Infra Red (FT-IR). The characterization using X-RD showed that the ZnO has an hexagonal crystal structure  with crystal size of 23.13 nm; 23.38 nm and 40.25 nm, while FT-IR spectra showed that there were Zn-O strain, C-O aliphatic, C-H bending, C-C aliphatic  and O-H bending vibrations. ZnO-activated carbon composite was applicated as photocatalyst to degradate  methylene blue by irradiatting  the compound with UV light for 5 hours. The  results showed that the ZnO-activated carbon composite at the ratio of 5:1 at optimum pH of 11 gave the highest percentage of methylene blue degradation which was of 99,97±0,02 %.
Keywords: ZnO-activated carbon composite, photocatalyst, photodegradation, and methylene blue